Through-the-thickness stress profiles in laminated composite and sandwich structure plates via unified formulation. (15th December 2016) - Caliri, Mauricio F.; Ferreira, Antonio J.M.; Tita, Volnei
Abstract: This paper presents a discussion on the through-the-thickness stress profiles of thick laminated plates and sandwich structures calculated with a particular generalized unified formulation. It consists on a finite element Unified Formulation (UF) with C-1 continuity of the transverse displacement field implemented in a four node plate element (CGF- Caliri's Generalized Formulation). The current works on unified formulations attempt to simplify and settle the development, use and choice of plate and shell theories. However, even using unified approaches, no generalizations base on specific problems are possible. For instance, the present work demonstrates that a non-linear plate theory may yield worse results when compared to a linear solution. It was found that, for a selected thick sandwich structure, a cubic layerwise theory provided a set of results 27% less accurate than the linear one. Moreover, when the through-the-thickness stress profiles are closely evaluated, the accuracy of the stress profiles are subjected to the solution method and not only the theory. Particularly, the effects of poor mesh resolution and boundary conditions are demonstrated in this work. Nevertheless, CGF is able to predict point-wise accurate results (less than 1% of deviation) even for the for transverse stresses variables.